Contribution of Marketing Mix and its Impact on Purchasing Decisions of Siantano Furniture Products - Eva Yuniarti Utami; Nurlaila Syarfiah Asfo; Rudi Kurniawan; Kushariyadi Kushariyadi; Andika Isma (Fundamental and Applied Management Journal, 2023)
This study aims to determine the effect and contribution of the marketing mix on purchasing decisions for Siantano Furniture Products that exist and are sold at PT Mega Indah Saru Timor (Misi Depo Bangunan) in Makassar City. The sample in this study were 96 Siantano furniture consumers who were coincidentally met by researchers and deemed suitable as respondents so that the Accidental Sampling method was used. Data collection was carried out using questionnaire, interview and documentation methods. The data analysis technique used is multiple linear regression analysis using Statistical Product and Servise Solution (SPSS) Version 25 and hypothesis testing using the F test and t test. The results of the study prove that part of the independent variables of the Marketing Mix, namely Product, Price, Place and Promotion have a positive and significant influence on the dependent variable, namely the Decision to Purchase Siantano Furniture Products at the Building Depot Mission in Makassar City. Products are the most dominant variable and have a significant effect on Purchasing Decisions for Siantano Furniture Products at the Building Depo Mission in Makassar City and are proven to be acceptable. Product is one of the variables that become the image of Siantano furniture which attracts consumers to buy these products.